TINJAUAN YURIDIS PEMBENTUKAN DAERAH OTONOMI BARU PROVINSI PAPUA SELATAN: Juridical Review Of The Establishment Of A New Autonomous Region Of The Province Of Southern Papua - Mochamad Ade Fahmi; Tri Sulistyowati (Reformasi Hukum Trisakti, 2025)
South Papua Province was established by Law No. 14 of 2022, enacted on July 25, 2022. This new province is a result of the division of Papua Province, which continues to generate public debate regarding the urgency of its expansion. This study examines the considerations of the central government and the House of Representatives in the formation of South Papua Province, and whether its creation complies with Law No. 23 of 2014 on Regional Government. The research uses a normative legal method based on secondary data, including primary and secondary legal materials. It is descriptive in nature, using qualitative analysis and deductive reasoning. The findings conclude that the government views the establishment of South Papua Province as a way to promote equitable development and improve service accessibility in Papua. However, administratively, the formation does not meet the basic and administrative requirements for a New Autonomous Region (DOB), such as having at least five regencies/cities and a three-year preparatory phase, as required by Law 23/2014. Despite this, the government proceeded with the expansion based on Law No. 2 of 2021, the Second Amendment to Law No. 21 of 2001 on Special Autonomy for Papua.